Individuals with headache present increased peripheral cefhalica and extracephalic sensitivity - Andrade, Rodrigo Sousa; Nogueira , Matheus Rafael Feques Ferreira; Castro, Ryan Pinheiro; Nascimento, Ana Lourdes Avelar; Carvalho, Sarah Tarcicia Rebelo Ferreira de; Pinho, Pedro Leonardo; Costa, Thiago Rafael Lima; Dibai, Daniela Bassi; Filho, Almir Vieira Dibai; Gonçalves, Maria Claudia (Headache Medicine, 2024)
Introduction: Individuals with headache present changes in the pain threshold due to pressure in the cervical region, however the literature remains controversial regarding the reduction of this parameter in the masticatory muscles. Objective: To evaluate peripheral sensitization of cephalic and extracephalic regions in individuals with and without headache. Materials and methods: Case-control study, with young adult individuals with and without headache, aged between 18 and 30 years old and excluding those with other chronic pain such as fibromyalgia, temporomandibular disorder and who had undergone previous orthognathic surgery, treatment for TMD or suffered trauma on the face. The Headache Screening Questionnaire was used to assess the frequency, intensity and duration of attacks and possible diagnosis of headache, and the Fonseca Anamnestic Index was used to verify the presence of temporomandibular disorder, considered as without TMD those who obtained